Systematic Review of Statistical Method Used in ICT Ethics Studies (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In any study or research, a research method plays an important role in obtaining good results. In this regard, statistical methods are essential for qualitative, quantitative, and mixed-method research. Generally, statistical methods involve mathematical formulas, models, and techniques used in analyzing raw research data. They extract information from research data and provides various ways to assess the robustness of research outputs. The findings could help researchers to better understand the appropriate statistical methods used for ICT ethics studies. The research field's growth contributes to various new methods in a study, especially in an ICT ethics issue. Each technique used brings different results to a study. As the research field develops and the number of studies increases, the scope of the areas expands.Therefore, this paper aims to investigate the use of statistical methods in ICT ethics studies. This study reviews the research done on ICT ethics for the years 2015 until 2020.  The research questions addressed in this study are:1) What statistical method is used in the fields of ICT ethics studies?, 2) What application areas in ICT ethics studies use the statistical method?, and 3) What research methods (quantitative, qualitative, and mixed) were used in the fields of ICT ethics studies.The findings revealed that quantitative is the most research methodused, followed by qualitative and mixed. The inferential statistical method was most employed, followed by the descriptive statistical method and other methods. Also, non-parametric was the most technique used compared to parametric.